Estimation of antigenotoxic properties of Ginger (Zingibe officinale) for DNA Damage after Exposure to Patulin in rats - Deef, Lamiaa Elsayed Mokhtar; El-Bakry, Kadry Abd-El kader; Habbak, Lotfy Zakaria; El-Naeli, Samia Salem (Acta Scientiarum. Health Sciences, 2023)
Patulin, a known fungal poison, is an important pollutant in apples and products derived from apples and fodder. Ginger improved the liver function and prevents hepatotoxicity against many toxins and used in treatment of various diseases. The genetic toxicity of patulin in the liver of rats using the comet assay in vivo was investigated and effect of ginger (Zingibe officinale) on DNA damage induced by patulin. Five groups of adult male Sprague Dawley rats were used. The rats were given 3.75 mg kg-1 intraperitoneal (i.p) patulin. The rats were treated with ginger at a dose (100 mg kg-1) for four weeks and eight weeks. DNA damage was measured in the liver of rats using a standard genetic toxicity tests comet assay. Tail length and percentage of tail DNA within the comet increased significantly (p <0.05) in patulin group (p =0.01), (p =0.000) respectively, compared with control group a time-dependent manner, indicating an increase in DNA damage. The liver tissue showed signs of improvement in DNA damage after treating rats with ginger. In conclusion, these results indicate that patulin is genotoxic at the injected dose and that liver is an important target organ. Instead, ginger therapy can reduce DNA damage in liver cells from the toxicity caused by patulin.